Integrating sex-and-gender in Zimbabwe’s Family, Religious and Moral Education syllabus - Gift Masengwe; Bekithemba Dube (Theologia Viatorum, 2025)
This article reviews and assesses the Family, Religious and Moral Education (FAREME) syllabus’ treatment of sex-and-gender (SnG) perspectives. Family, Religious and Moral Education lacks sufficient SnG socialisation perspectives, and we propose to use the Theory of Change (ToC) to integrate these issues. Results suggest that 10% quantitative integration of SnG content and objectives across all FAREME levels as well as qualitative combination of SnG differences can empower learners to become advocates for SnG equality and respectful religious practices in Zimbabwean schools. This study is informed by qualitative research methodology. The ToC is the theoretical framework used to support the unbiased integration of SnG-related issues into this qualitative study of the FAREME syllabus. Theory of Change helps identify, select, place, mentor and monitor how SnG issues are holistically integrated into the school syllabus. The review process advocates for a 10% quantitative integration target of SnG content and objectives across all levels, considering there are only 10 cross-cutting issues in the FAREME syllabus. Moreover, the study emphasises the qualitative combination of biological and socio-cultural differences within religious phenomena throughout the syllabus. This approach allows learners to develop a comprehensive understanding of SnG perspectives.